Gross and histopathological evaluation of runting stunting syndrome in a broiler farm - Aung Tun Khaing; Nwe New Htin; Abdulnasir Tijjani; Yusuf Abba; Faez Firdaus Abdullah Jesse; Erkihun Aklilu; Teng Jinghui; Konto Mohammed; Lawan Adamu; Mohammad Abubakar Sadiq (2014)
A poultry farmer reported a case of abnormal growth among 17 to 25 days old broilers chicks in his farm